The Implementation I-SETS based Learning Tools to Improve Learning Outcomes and Problem Solving Skills on Ecosystem Material in MTs - Lilis Erfianti; Ngabekti, Sri; Saptono, Sigit (Universitas Negeri Semarang, 2024)
The research aims to identify the characteristics, validity, readability, and effectiveness of I-SETS teaching devices as well as improve learning outcomes and skills in solving ecosystem material problems. This study used experimental and control classes and then measured the results of the pretest and post test with the N-gain formula. The results of the research showed that the teaching device based on I-SETS has the characteristics of ecosystem material content that is integrated with Islamic values in the Quran and hadith and applies SETS learning measures. (Science, Environment, Technology, and Society). The results of the data analysis showed that in the experimental and control classes, the percentage of N-gain test results was in the range of 0.3-0.7 for MTsN Semarang and MTsN Salatiga with moderate criteria. There was an improvement in environmental problem-solving skills in the experimental class compared to the control class with medium criteria, as well as an elevation of attitudes toward the environment. Students showed excellent criteria. Based on research results, I-SETS-based teaching devices are valid and usable and can improve learning outcomes and skills to solve ecosystem material problems.